Birth outcomes associated with maternal exposure to metals from informal electronic waste recycling in Guiyu, China. (April 2020) - Kim, Stephani S.; Xu, Xijin; Zhang, Yuling; Zheng, Xiangbin; Liu, Rongju; Dietrich, Kim N.; Reponen, Tiina; Xie, Changchun; Sucharew, Heidi; Huo, Xia; Chen, Aimin
Highlights: E-waste is a growing problem around the world. Neonates born in an e-waste recycling community in China are exposed to heavy metals. These neonates had smaller head circumference, BMI, and Ponderal Index. Must find ways to protect the most vulnerable groups in communities that recycle e-waste. Abstract: Background: Informal electronic waste (e-waste) recycling is a rapidly growing industry. Informal e-waste recycling creates a mixture of chemicals that can be harmful to humans, especially vulnerable populations like pregnant women and young children. Objectives: We aimed to analyze the associations between birth outcomes and living in a community with a history of informal e-waste recycling. Methods: The e-waste Recycling Exposure and Community Health (e-REACH) Study enrolled pregnant women in Guiyu, an informal e-waste recycling site (n = 314), and an unexposed control site (Haojiang) (n = 320) at delivery. We analyzed maternal whole blood samples for lead (Pb), cadmium (Cd), chromium (Cr), and manganese (Mn). We captured data in newborns on birth weight, birth length, head circumference, body mass index (BMI), and Ponderal Index (PI). We compared the birth outcomes between sites after adjustment for covariates, and examined the associations with individual and the mixture of metals. Results: The neonates from Guiyu had smaller head circumference (adj β −1.96 cm, 95% CI −2.39, −1.52), BMI (adj β −0.77 kg/m 2, 95% CI −1.03, −0.51), and PI (adj β −2.01 kg/m 3, 95% CI −2.54, −1.47). Birth weights were lower in Guiyu compared to Haojiang, but the difference was not significant (β −51, 95% CI −132, 29). Cumulative exposure to metals was related to lower head circumference, BMI, and PI, but not related to birth weight. Discussion: We observed slight and statistically significant differences in the head size, BMI, and PI of neonates, but not birth weight, from Guiyu when compared to neonates from Haojiang. Cumulative metal exposure may partially account for the findings.